2017
DOI: 10.1101/186460
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aberrant brain response after auditory deviance in PTSD compared to trauma controls: An EEG study

Abstract: Part of the symptomatology of post-traumatic stress disorder (PTSD) are alterations in arousal and reactivity which could be related to a maladaptive increase in the automated sensory change detection system of the brain. In the current EEG study we investigated whether the brain's response to a simple auditory sensory change was altered in patients with PTSD relative to trauma-exposed matched controls who did not develop the disorder. Thirteen male PTSD patients and trauma-exposed controls matched for age and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Social expectations themselves are learned from one's past social experiences; thus, the use of social expectations to inform precision of perceptual priors may explain some of the known relationships between trauma exposure, locus of control, agency, and ability to control one's hallucinations 109 . Indeed, past trauma has been shown to affect processes related to detection of basic auditory stimulus features 110 . These processes also change with affective state 111 .…”
Section: Potential Cognitive Computational and Neural Mechanismsmentioning
confidence: 99%
“…Social expectations themselves are learned from one's past social experiences; thus, the use of social expectations to inform precision of perceptual priors may explain some of the known relationships between trauma exposure, locus of control, agency, and ability to control one's hallucinations 109 . Indeed, past trauma has been shown to affect processes related to detection of basic auditory stimulus features 110 . These processes also change with affective state 111 .…”
Section: Potential Cognitive Computational and Neural Mechanismsmentioning
confidence: 99%
“…More specifically, recalling that the estimated second subject-level component is a measures of whole-brain theta power, if a person has a history of trauma, the higher his/her theta power, the lower their expected dissociation level. Theta power is associated with memory and emotional control and has been shown to be elevated in participants with a history of post traumatic stress disorder (Bangel et al, 2017). This result may suggest that during instructed rumination, if a person has a history of trauma, not engaging memory related circuitry, perhaps failing to reinvoke trauma recollections, even when a person wants to, may involve dissociation.…”
Section: Regression Model and Resultsmentioning
confidence: 99%
“…The outcome of our study differs from the findings of similar previously published studies. In particular, larger MMNs have been linked with PTSD in previous studies 8-10 that all used standard oddball protocols. In contrast, the only other study that employed a multifeature protocol 11 found reduced MMN amplitudes in PTSD, in particular when the deviants differed from standard sounds in the dimensions gap and duration.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly larger MMNs (again elicited by frequency deviants) were also found in individuals that developed PTSD after experiencing a destructive earthquake compared with a control group that did not develop PTSD after the same event. 9 A more recent study by Bangel et al 10 compared trauma-exposed males with PTSD with a trauma-exposed control group without PTSD and found enhanced MMNs using deviants that differed from standards in both frequency and duration. These findings have been interpreted as increased sensitivity to stimulus changes in PTSD as a result of hypervigilance and hyperarousal.…”
Section: Introductionmentioning
confidence: 99%